The last voyage of Capt. Sir John Ross, R. N. Knt. to the Arctic regions; for the discovery of a north west passage; performed in the years 1829-30-31-32 and 33. To which is prefixed an abridgement of the former voyages of Captns. Ross, Parry & other celebrated navigators to the northern latitudes. - Huish, Robert, 1777-1850. comp.; Victory (Ship) (London, J. Saunders, 1836)
Added t.-p., engr. Mode of access: Internet.